ATM inhibition enhances Auranofin-induced oxidative stress and cell death in lung cell lines - Ehrenfeld, Vanessa (PLoS One, 2020)
Ataxia-Telangiectasia (A-T), a pleiotropic chromosomal breakage syndrome, is caused by the loss of the kinase Ataxia-telangiectasia mutated (ATM). ATM is not only involved in the response to DNA damage, but also in sensing and counteracting oxidative stress. Since a disturbed redox balance has been implicated in the pathophysiology of A-T lung disease, we aimed to further explore the interplay between ATM and oxidative stress in lung cells. Using a kinetic trapping approach, we could demonstrate an interaction between the trapping mutant TRX1-CS and ATM upon oxidative stress. We could further show that combined inhibition of thioredoxin reductase (TrxR) and ATM kinase activity, using Auranofin and KU55933 respectively, induced an increase in cellular reactive oxygen species (ROS) levels and protein oxidation in lung cells. Furthermore, ATM inhibition sensitized lung cells to Auranofin-induced cell death that could be rescued by ROS scavengers. As a consequence, targeted reduction of ATM by TRX1 could serve as a regulator of oxidative ATM activation and contribute to the maintenance of the cellular redox homeostasis. These results highlight the importance of the redox-active function of ATM in preventing ROS accumulation and cell death in lung cells.